2016
DOI: 10.1597/14-308
|View full text |Cite
|
Sign up to set email alerts
|

7q21.11 Microdeletion in a Neonate with Goldenhar Syndrome: Case Report and a Literature Review

Abstract: The oculoauriculovertebral spectrum or Goldenhar syndrome is characterized by varying degrees of prevalently unilateral underdevelopment of the craniofacial structures (orbit, ear, and mandible) in association with vertebral, cardiac, renal, and central nervous system defects. We report on a term neonate with a partial monosomy 7q21.11 with marked hemifacial microsomia, facial clefting, and spinal anomaly. The estimated size of the monosomic region of 7q21.11 was approximately 55 kilobases. This is the first r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In the literature review, 17 articles reporting genomic imbalances in individuals with CFM were found. Among them, four studies were case series (Beleza‐Meireles et al, 2015; Bragagnolo et al, 2018; Callier et al, 2008; Rooryck et al, 2010) and 13 were case reports (Brun et al, 2012; Colovati et al, 2015; Dos Santos et al, 2014; Gimelli, Cuoco, Ronchetto, Gimelli, & Tassano, 2013; Guida et al, 2015; Lafay‐Cousin et al, 2009; Puvabanditsin et al, 2016; Quintero‐Rivera & Martinez‐Agosto, 2013; Rooryck et al, 2010; Tan et al, 2011; Torti, Braddock, Bernreuter, & Batanian, 2013; Xu, Fan, & Siu, 2008; Zielinski et al, 2014). There were two individuals described twice in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature review, 17 articles reporting genomic imbalances in individuals with CFM were found. Among them, four studies were case series (Beleza‐Meireles et al, 2015; Bragagnolo et al, 2018; Callier et al, 2008; Rooryck et al, 2010) and 13 were case reports (Brun et al, 2012; Colovati et al, 2015; Dos Santos et al, 2014; Gimelli, Cuoco, Ronchetto, Gimelli, & Tassano, 2013; Guida et al, 2015; Lafay‐Cousin et al, 2009; Puvabanditsin et al, 2016; Quintero‐Rivera & Martinez‐Agosto, 2013; Rooryck et al, 2010; Tan et al, 2011; Torti, Braddock, Bernreuter, & Batanian, 2013; Xu, Fan, & Siu, 2008; Zielinski et al, 2014). There were two individuals described twice in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature review, 17 articles reporting genomic imbalances in individuals with CFM were found. Among them, four studies were case series (Beleza-Meireles et al, 2015;Bragagnolo et al, 2018;Callier et al, 2008;Rooryck et al, 2010) and 13 were case reports (Brun et al, 2012;Colovati et al, 2015;Dos Santos et al, 2014;Gimelli, Cuoco, Ronchetto, Gimelli, & Tassano, 2013;Guida et al, 2015;Lafay-Cousin et al, 2009;Puvabanditsin et al, & Martinez-Agosto, 2013;Tan et al, 2011;Torti et al, 2013;Xu et al, 2008 Although the VOUS do not enable concluding the diagnosis, these genomic imbalances must not be scrapped; the reanalyzes of these VOUS might be important, because their classification may change to either a benign or pathogenic category as the clinical databases are updated (Nowakowska, 2017;Palmer et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…asymmetry and microtia, there is no consensus regarding clinical criteria for diagnosis 7 or genetic cause. 8 Several genomic and chromosomal alterations have been reported in individuals with clinical diagnosis for OAVS, 6,[9][10][11] and there is no gold standard modality for molecular diagnosis in OAVS. Heterogeneity is a hallmark of OAVS.…”
Section: Introductionmentioning
confidence: 99%